Kebijakan Luar Negeri Indonesia: Studi Kasus Penerimaan Pengungsi Rohingya Asal Myanmar Tahun 2020-2022 - Indradipradana, Ramaldy Krisna; Haridha, Frieska (Universitas Diponegoro, 2023)
The Rohingya ethnic conflict is one of the conflicts that occurred due to instability in political life and society in Myanmar. The cause of this conflict was discrimination against the Rohingya ethnic group, which resulted in quite a few Rohingya people fleeing. In 2015, Indonesia, Malaysia, and Thailand agreed to allow Rohingya refugees into their territories. However, Thailand and Malaysia in 2020-2022 did not permit Rohingya refugees to enter their territory. The rejection of these two countries caused Indonesia to become the only country in the world that accepted Rohingya refugees even though it did not ratify the 1951 Convention and the 1967 Protocol. This qualitative research focuses on discussing the factors that prompted Indonesia to accept Rohingya refugees in 2020-2022 with internet-based research in data collection. In addition, this research uses foreign policy from Kegley and Raymond (2012). This research shows that four factors encourage Indonesia to accept Rohingya refugees: geostrategic position, economic conditions, type of government, and decisions & leadership capacity.